Globalized e-learning cultural challenges - Edmundson, Andrea 1955-.; Gale Group (Hershey, Pennsylvania Information Science Publication, 2007)
"This book's purpose is to inform educators and instructional designers of issues and cultural misunderstandings that could hinder the effective transfer of knowledge when e-learning is exported to other cultures. Addressing these cultural challenges will enhance the effectiveness of e-learning, thereby supporting the societal benefits of increased access to education at a global level."--Provided by publisher.
The big picture : culture and e-learning from global perspectives -- Western philosophies and theoretical foundations in e-learning -- Language and semiotics -- Addressing issues of cross-cultural instructional design -- Conclusion.
Electronic reproduction.
Keywords: Virtual reality in education -- Cross-cultural studies; Internet in education -- Cross-cultural studies; Distance education -- Computer-assisted instruction -- Cross-cultural studies; Multicultural education -- Computer-assisted instruction; Intercultural communication; Electronic books